THE EFFECT OF EXPORT AND IMPORT ON INFLATION IN INDONESIA PERIOD 1990-2016 - Nurul Ulfa; Tarmizi Abbas (LPPM Universitas Malikussaleh, 2018)
This research conducted to determine the effect of effect of exports and imports on inflation in Indonesia in the period 1990-2016. The data used in this study are time series in the periode 1990-2016 obtained from the BPS Indonesia and Bank Indonesia. Data are then analyzed by using multiple linear regression. The results showed that exports did not affect inflation. Imports have a significant and positive effect on inflation in Indonesia in the period 1990-2016.